The concurrence of the current postanalytical phase management with the national recommendations : a survey of the Working Group for Postanalytics of the Croatian Society of Medical Biochemistry and Laboratory Medicine - Jokic, Anja (Array, 2021)
The detection and prevention of errors in the postanalytical phase can be done through the harmonization and standardization of constituent parts of this phase of laboratory work. The aim was to investigate how well the ongoing management of the postanalytical phase corresponds to the document "Post-analytical laboratory work: national recommendations" in Croatian medical biochemistry laboratories (MBLs). All 195 MBLs participating in the national external quality assessment scheme, were invited to undertake a part in a survey. Through 23 questions the participants were asked about management of the reference intervals (RI), delta check, reflex/reflective testing, postanalytical quality indicators and other parts of the postanalytical phase recommended in the national recommendations. The results are presented in numbers and percentages. Out of 195 MBLs, 119 participated in the survey, giving a response rate of 61%. Not all of the respondents provided answers to all the questions. Delta check has not been used in 59% (70/118) of the laboratories. Only 22/113 (20%) laboratories use reflex and/or reflective testing. In 53% of the laboratories, critical results were reported within 30 minutes of the confirmation of the results. In 34% (40/118) of the laboratories, turnaround time and reporting of critical results are two most often monitored postanalytical quality indicators. The results showed the critical results reporting and monitoring of postanalytical quality indicators are in the line with the recommendations. However, the management of RI verification, the use of delta check and reflex/reflective testing still must be harmonized among Croatian MBLs.